Coil occlusion of PDA in patients younger than 1 year: Risk factors for adverse events - Tomita, Hideshi; Uemura, Shigeru; Haneda, Noriyuki; Soga, Takashi; Matsuoka, Takashi; Nishioka, Takashiro; Yazaki, Satoshi; Hatakeyama, Kinya; Takamuro, Motoki; Horita, Norihisa (Journal of cardiology, 2009)
Transcatheter occlusion of infantile patent ductus arteriosus (PDA) challenges the interventionist. To analyze the risk factors for adverse events from this procedure in patients younger than 12 months. We retrospectively analyzed data on 32 patients younger than 12 months in whom transcatheter coil occlusion of a PDA was attempted. Ages ranged from 1 to 11 (median, 7) months and body weight from 1.2 to 10 (6.0) kg. The minimum ductal diameter ranged from 1.0 to 4.6 (3.3) mm and pulmonary to systemic flow ratio from 0.7 to 12.5 (2.2). Major adverse events were defined as those requiring surgery, while minor adverse events included transient hemolysis not needing treatment, coil migration with successful transcatheter retrieval, and mild left pulmonary artery (PA) stenosis. We determined whether any factors such as age, body weight, minimum PDA diameter, angiographic type, operator, and use of a 0.052-in. Gianturco coil related to the occurrence of adverse events. In two patients, coils could not be deployed in the appropriate position. They underwent surgery following transcatheter retrieval of coils. Coils were successfully deployed in the other 30 patients, however, one patient developed persistent hemolysis that required surgical retrieval of the coils and closure. PDA was completely closed in the other 29 patients (clinical success rate, 91%). Thus, there were three major adverse events, while minor adverse events occurred in five patients. Univariate analysis did not identify any single factor that contributed to either major, minor, or total adverse events. However, all major adverse events occurred in patients under 6 months and less than 6 kg body weight with a minimum duct diameter of more than 3.5 mm. Transcatheter coil occlusion of PDA is feasible in selected patients younger than 1 year. A minimum diameter more than 3.5 mm in patients under 6 kg may be a risk factor for major adverse events.